THE INFLUENCE OF FINANCE LITERACY, EASY PERCEPTION AND RISK TO INTEREST USE FINTECH PAYMENTS ( PAYLATER) ON APPLICATION SHOPEE - Harahap, Khairunnisa (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this research is to determine and analyze the influence of Financial Literacy on Interest in Using Fintech Payment (Paylater) on the Shopee Application. To find out and analyze the Perception of Ease of Interest in Using Fintech Payment (Paylater) on the Shopee Application. To find out and analyze the risks regarding interest in using Fintech Payment (Paylater) on the Shopee Application. To find out and analyze the influence of Financial Literacy, Perception of Convenience and Risk on Interest in Using Fintech Payment (Paylater) among students at the Faculty of Economics and Business, Muhammadiyah University, North Sumatra. In this research, an associative approaches is used to determine the relationships between each variables. The data is presented in the form of quantitative data, namely testing and analyzing the data by calculating numbers and then drawing conclusions and testing. In this research, the objects studied were students of the 2019 Stambuk Management Study Program, Faculty of Economics and Business, Muhammadiyah University, North Sumatra with a population of 612 people and a sample of 86 people with sampling using the Slovin formula. The results of this research are that financial literacy has been significant effect on interest in using Fintech Payment (Paylater) on the Shopee application. Perception of Convenience has a significant effect on Interest in Using Fintech Payment (Paylater) on the Shopee Application. Risk has a significant effect on interest in using Fintech Payment (Paylater) on the Shopee application. And Financial Literacy, Perception of Convenience and Risk have a significant effect on Interest in Using Fintech Payment (Paylater) among students at the Faculty of Economics and Business, Muhammadiyah University, North Sumatra.